COURT PROCEDURES AND QĀḌĪ SYSTEM IN ISLAMIC LAW (European Journal of Interdisciplinary Research and Development, 2026)
This article examines the distinctive features of judicial proceedings from the early Islamic period up to the nineteenth century, the functions of qāḍīs, the requirements imposed on their personal qualities, as well as the depiction of judicial ethics in the sources of Islamic law.